With the word, the user with disability and the reality experienced in libraries - Wellichan, Danielle da Silva Pinheiro [UNESP]; Manzini, Eduardo Jose [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2023)
The user can be considered an important source of information for libraries with regard to the elaboration and direction of products and services developed for him, especially if he is a person with a disability. However, despite the recommendation and guidance in the literature, this user is still not served as expected with regard to access and accessibility in the library. From this perspective, the objective was to know, together with nine users with disabilities, the relationship between them and libraries, from childhood to the current stage, and how, in their view, library professionals could offer more inclusive services. As a library user study, the construction of this text was sought through a theoretical framework that brought together materials in portuguese, without a time frame, associated with the recording of videos carried out by the guest users themselves. The results showed two situations in the same reality: on the one hand, users who found support for their development in school libraries; on the other hand, those who only knew it in Higher Education, when they unite in pointing out that the university library offers better conditions for use and frequency, even in the midst of some difficulties. The study allowed us to conclude that this relationship can be satisfactory at several points, especially if the information user is heard and collaborates in its inclusive in libraries.
Keywords: special education; libraries; disabled users